Antiepileptic Drugs, Reaction Time, and Impulsivity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The effects of antiepileptic drugs (AED) on reaction time, attention, and impulsivity in 111 epileptic children, aged 5 to 13 years, are reported from the Children's Hospital of Los Angeles and University of Southern California School of Medicine.